2017
DOI: 10.4314/ijbcs.v10i6.16
|View full text |Cite
|
Sign up to set email alerts
|

Analyse des connaissances endogènes et des déterminants de la production de la patate douce [<i>Ipomoea batatas</i> (L.)], une culture à haute valeur socioculturelle et économique au Bénin

Abstract: La patate douce est une culture négligée alors que sa contribution dans la sécurité alimentaire est importante au Bénin. Ce travail a permis d'évaluer les connaissances paysannes sur la diversité, les contraintes de production, les pratiques agricoles de conservation des tubercules et de gestion du système semencier de la patate à travers 35 villages du Sud-Bénin. La méthodologie a consisté en une recherche participative par des entretiens individuels et de groupe. Les résultats obtenus ont permis de recenser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…Farmer' preferences for sweet potato varieties were not only influenced by the yield performance but also the variety's commercial value, notably root size, as well as market demand for the variety (Adeola et al, 2019;Mwanga et al, 2021b;Shumbusha et al, 2020;). The findings confirmed that yield was not the only factor in farmers' sweet potato variety selection (Doussoh et al, 2017;Low et al, 2017a;Placide et al, 2015;Sanoussi et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Farmer' preferences for sweet potato varieties were not only influenced by the yield performance but also the variety's commercial value, notably root size, as well as market demand for the variety (Adeola et al, 2019;Mwanga et al, 2021b;Shumbusha et al, 2020;). The findings confirmed that yield was not the only factor in farmers' sweet potato variety selection (Doussoh et al, 2017;Low et al, 2017a;Placide et al, 2015;Sanoussi et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Kaguongo et al (2012) reported similar results in his study highlighting that the origin of the farmer as well as the level of commercialization of a variety influences its adoption. For Doussoh et al (2017), high commercial value was one of the important selection criteria for sweet potato varieties intended for production in Benin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepper (Capsicum annuum), tomato (Lycopersicon esculentum) and bitter-leaf (Vernonia amygdalina) are sometimes grown around the houses. Tomato is one of the most important productions in Benin (Doussoh et al, 2017). Tuber and root crops are yam (Dioscorea batatas), cassava (Manihot esculenta) and sweet potatos (Ipomoea batatas).…”
Section: Vegetation and Crop Production Systemsmentioning
confidence: 99%
“…Sweet potato (Ipomoea batatas L) which originated from Central America is a dicotyledonous plant that belongs to the family Convolvulaceae (Shekhar et al, 2015). Sweet potato is the world's seventh most important food crop (Mussoline and Wilkie, 2017) and cultivated in tropical, subtropical and temperate regions ( Shekhar et al, 2015;Doussoh et al, 2016) in more than 100 countries in South East Asia, Africa, Oceania, and Latin America regions and China. The world's leading sweet potato producer with more than 75% of the world's production is China (FAO, 2016).…”
Section: Introductionmentioning
confidence: 99%